Behavioral spillover between the use of reusable shopping bags and recycling at home: A field experiment - Claudia Arias; Carlos A. Trujillo (PLoS ONE, 2025)
This study examines positive behavioral spillover between waste-related behaviors that vary in complexity. Specifically, we test whether encouraging a relatively simple behavior—using reusable shopping bags—can lead to increased adoption of a more complex behavior, such as recycling. To investigate this, we conducted a longitudinal field experiment. Additionally, we explored the moderating roles of three individual-level constructs: Perceived Difficulty, Self-efficacy, and Perceived Consumer Effectiveness. Our findings show that positive spillover occurs for recycling at home, but not for recycling elsewhere. Moreover, Perceived Difficulty strengthens this effect, while Perceived Consumer Effectiveness diminishes it. We conclude by discussing how these insights can inform public and private interventions aimed at promoting recycling.